Optimization of Triterpenoid Extraction from Ganoderma lucidum by Ethanol‐Modified Supercritical Carbon Dioxide andthe Biological Properties of the Extract. Issue 8 (21st February 2022) - Dat, Tran Do; Viet, Nguyen Duc; Thanh, Vuong Hoai; Linh, Ngo Thi Thuy; Ngan, Nguyen Thi Kim; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this work, the supercritical CO2 extraction methodology was utilized to extract triterpenoids from Ganoderma lucidum ( G. lucidum ). Box‐Behnken experimental design was employed in order to optimize the extraction conditions. Results showed that the highest triterpenoid content of 4.122±0.09 mg/g could be obtained under extraction conditions including pressure of 312 bar, temperature of 53 °C, solvent‐to‐sample ratio 1.74 mL/g, and time of 120 min. The extract was analyzed using Fourier transform infrared spectrometry, gas chromatography‐mass spectrometry, and scanning electron microscopy to confirm the support of the supercritical CO2 in disrupting the cell walls of G. lucidum . The 2, 2‐diphenyl‐1‐picrylhydrazyl radical scavenging was carried out for the antioxidant evaluation. The antibacterial properties of the extract were evaluated against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella enterica with inhibition zone of 21.33, 21.67, 23.67, and 14.00 mm, respectively. Furthermore, the extract was able to suppress the development of hepatocellular carcinoma, breast carcinoma, and epidermic carcinoma the half‐maximal inhibitory concentration values of 50.32, 75.34, and 113.16 μg/mL, respectively. Therefore, the present investigation demonstrates the potential use of G. lucidum, which is high in triterpenoid in the manufacture of functional foods, health promotion, against bacterial infections, and cancer therapy. Abstract : This study describes the process of extracting triterpenoid from Vietnamese Ganoderma lucidum by supercritical CO2 technique. Factors such as pressure, temperature, solvent:material ratio, and time affecting triterpenoid content were studied to optimize extraction conditions. In addition, the extract has been tested for its antioxidant, antibacterial, and cancer cell inhibitory activities for application in disease treatment support and functional foods.